2008
DOI: 10.3126/jnbs.v4i1.1028
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Outsourcing: Issues and Challenges

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Because HR outsourcing d e c i s i o n s i n c r e a efficiency; they have time to spend on their skill development (Delmotte and Sels, (2008). Kodwani (2007) also found that decision of outsourcing HR activities reduces the burden of employees and increases the interaction between employer and employees.…”
Section: Correlation Between Variablesmentioning
confidence: 99%
“…Because HR outsourcing d e c i s i o n s i n c r e a efficiency; they have time to spend on their skill development (Delmotte and Sels, (2008). Kodwani (2007) also found that decision of outsourcing HR activities reduces the burden of employees and increases the interaction between employer and employees.…”
Section: Correlation Between Variablesmentioning
confidence: 99%
“…First, outsourcing enables an organisation to relinquish some of its non-core activities to focus on developing greater competencies in its core-activities (Domberger 1998;Venkatraman 1997). By outsourcing its non-core activities, an organisation frees internal resources that will help it to focus and improve on its corecompetencies (Kodwani 2007), and be able to gain or reinforce competitive advantage in its market. Secondly, results of many studies show that outsourcing enables an organisation to become more efficient by reducing its operational costs.…”
Section: Literature Review 21 Outsourcingmentioning
confidence: 99%
“…Outsourcing allows a firm to focus on building core strengths while letting go of non-core tasks (Venkatraman, 1997;Domberger, 1998;Gibler and Black, 2004). According to Kodwani (2007), outsourcing non-core activities frees up internal resources that can be used to improve core capabilities and achieve or maintain competitive advantage in the market. World Bank (1997) reviewed the rules for selecting and hiring consultants.…”
Section: Introductionmentioning
confidence: 99%